Potato (Solanum tuberosum L.) flour enriched with date palm fruit (Phoenix dactylifera L.) powder and bean milk for cookies production - Akhobakoh, Mikhail; Zing Zing, Bertrand; Ngatchou, Alban; Mbassi, Josiane Emilie Germaine; Nchanji, Eileen Bogweh (Scientific Research Publishing, Inc., 2022)
This study emphasizes the formulation of three types of cookies viz potato flour with date powder and bean milk (PDBM), potato flour with sugar and bean milk (PSBM), and potato flour, sugar, and eggs as control. After the substitution, the highest protein content was observed in PDBM (1.78 ± 0.12)% followed by PSBM, (1.35 ± 0.01)% and the lowest was in the control (0.91 ± 0.55)%. Moreover, cookies fortified with date palm powder increased the carbohydrate and fat contents compared to the control and significantly increased the calorific value of PDBM. The formulated cookies were significantly higher (p < 0.05) in iron (39.95 ± 3.00) mg/100 g and zinc (13.65 ± 1.61) mg/100 g in PDBM compared to other cookies. The date palm powder incorporated in cookies significantly increases the darkening of biscuits during cooking. The organoleptic characteristics of PDBM and PSBM were rated overall best when specific parameters were tested. With the shortage of wheat and importation constraints, an alternative provides a great market opportunity for local products like potatoes and beans. In addition, fortifying food products as cookies eaten by all will contribute to a more food and nutrition-secured world.